Anemia During Pregnancy: A Study Between Booking Visit and Delivery from South Africa - Hoque, AKM Monjurul; Hoque, Maariyah; Hoque, Muhammad Ehsanul; Naidoo, Kantharuben; Anwar, Mir (Al-Sihah: The Public Health Science Journal, 2024)
In South Africa (SA), the highest prevalence of anemia in pregnancy of 43% is reported in the KwaZulu-Natal province at initial Antenatal Care (ANC) visit. To prevent anemia during pregnancy, iron supplementation is provided during pregnancy. There is no study undertaken to compare anemia at booking ANC visit with the rate at delivery. This study aims to estimate the prevalence of anemia at ANC booking and delivery, and identify risk factors. Facility based retrospective cohort study was conducted among pregnant women who delivered at the health facility. Data were coded, captured and analysed using SPSS software. Logistic regression was performed to determine predictors for anemia. Results showed significantly higher prevalence of anemia (36.5%) at initiation of ANC compared to 18.6% at delivery (p<0.05). The mean Hb increased from 11.4 g/dL at ANC initiation to 12.3 g/dL at delivery. Logistic regression showed that women without syphilis (OR=0.14, p=0.014) and those initiating ANC early (OR=0.35, p=0.018) had lower odds of anemia. HIV-positive women (OR=4.2, p=0.022) and those anaemic at booking (OR=10.84, p<0.001) had higher odds of anemia at delivery. Pregnant women aged 20–24 years were less likely (OR=0.34, p=0.041) to have increased Hb, while those without syphilis at ANC booking had lower odds (OR=0.46, p=0.04) of decreased Hb. ANC initiation, screening and treatment of HIV and syphilis infection must be strengthened.